Tugas Berbasis Proyek untuk Melatih Keterampilan Mengajar Mahasiswa Calon Guru Saat Pandemi Covid-19 - Hikmawati Hikmawati; Haerunisyah Sahidu; Kosim Kosim (Indonesian Journal of Teacher Education, 2020)
The purpose of this study was to describe the teaching skills of prospective physics teacher students during the COVID-19 pandemic through project-based assignments. This type of research is pre-experimental with the design of One Group Pretest and Posttest. The subjects of this study were 9 students who took the Micro Teaching course in Class E in the Academic Year 2019/2020 at the Physics Education Study Program, University of Mataram. The instrument used was a student teaching video evaluation sheet. The basic teaching skills that are assessed consist of 8 components, namely opening lessons, managing classes, providing reinforcement, asking questions, explaining lessons, using instructional media, holding variations, and closing lessons. Scoring scores for each component use a scale of 5, while the percentage value obtained through raw scores divided by a maximum score multiplied by 100. The results of the study showed that the lowest component value of teaching skills at pretest was classroom management skills of 60 and the highest was closing skills at 71, whereas the lowest value of the components of teaching skills at posttest was classroom management skills by 80 and the highest was the use of learning media skills by 91. The average value of students' teaching skills at pre-test was 67 while at posttest was 86. Thus, giving project-based assignments improve the teaching skills of prospective physics teacher students while the COVID-19 pandemic is 19 points, with the highest component of teaching skills being the use of instructional media.